The interpersonal communication approach to HIV/AIDS prevention: strategies and challenges for faith-based organizations. - Muturi, Nancy W. (My University, 2011)
This study examines the interpersonal communication approach to HIV/AIDS prevention within Faith-Based Organizations (FBOs) in Jamaica. Applying concepts from the social influence and social learning theories, the study examines communication strategies, challenges and concerns that religious leaders face in their communication efforts. Data gathered qualitatively through focus groups and in-depth interviews indicate that FBOs are social and cultural entities with potential to influence knowledge,attitude and behaviour for HIV/AIDS prevention. However, issues related to content, context, culture, the prevailing AIDS-related stigma alongside religious leaders’ personal characteristics hamper their communication initiatives. Capacity building of leaders as HIV/AIDS communicators and behaviour change facilitators and a collaborative effort between FBOs and health organizations would enhance their HIV/AIDS response.
Keywords: HIV/AIDS prevention; Faith based organizations; Interpersonal communication